Expression of interleukin-6 by intestinal enterocytes. Issue 12 (December 1993) - Jones, S C; Trejdosiewicz, L K; Banks, R E; Howdle, P D; Axon, A T; Dixon, M F; Whicher, J T
Abstract : AIMS–To investigate the cellular source of the cytokine interleukin-6 (IL-6) in the small and large intestines of patients with inflammatory bowel disease, coeliac disease, and in controls. METHODS–IL-6 was detected in frozen sections of bowel by single and double label indirect immunofluorescence using rabbit polyclonal and murine monoclonal anti-IL-6 antibodies. The murine monoclonal antibodies RFDR1 (anti-MHC class II) and UCHT1 (anti-CD3) were used to localise macrophages and T lymphocytes, respectively. Lipopolysaccharide stimulated peripheral blood monocytes were used as positive control cells for IL-6 protein. RESULTS–IL-6 was demonstrated in the small and large intestine of patients with inflammatory bowel disease, coeliac disease, and in controls. The protein was present predominantly in enterocytes and colocytes in normal and inflamed mucosa, but not in the infiltrating inflammatory cells of the lamina propria. There were no discernable differences between patients with inflammatory bowel disease or coeliac disease and controls, nor between small and large bowel mucosa. Incubation of antibody with recombinant human IL-6 protein abolished the labelling. IL-6 protein was also present in lipopolysaccharide stimulated peripheral blood monocytes. CONCLUSIONS–The data suggest that enterocytes and colocytes may play an active part in the immune response of the gut. The presence of IL-6 in both inflamed and non-inflamed small and large intestine requires further investigation into the function of this cytokine in the gut.